2015
DOI: 10.1134/s1067413615030029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of the building activity of Canadian and European beavers in northern European Russia

Abstract: The building activity of Canadian and European beavers has been analyzed in the north of Euro pean Russia (southern Karelia). The results show that, under similar orographic, edaphic, and hydrological conditions, both species build their lodges and dams with equal frequencies. It is concluded that the building activity of beavers is a response of these animals to specific features of their environment, rather than a spe cies specific manifestation of the building instinct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…Based on the results of the questionnaire (114 beaver territories, 458 beaver dams) and the detailed field survey (12 beaver territories, 51 beaver dams), an overview of the dam building activities of beavers in the streams of Bavaria was obtained. Our findings revealed that 90% of the beaver dams were observed in small streams with a width ranging from 2 to 11 m and 59% of the streams were in a depth range of 0.5 to 1 m. These results coincide with observations from other studies, which showed water depths of less than one meter and variable widths ranging between 0.5 and 46 m [16,18,[43][44][45]. In Bavaria, beavers show similar activity patterns as observed in other regions.…”
Section: Survey and Analysis Of Beaver Territoriessupporting
confidence: 90%
“…Based on the results of the questionnaire (114 beaver territories, 458 beaver dams) and the detailed field survey (12 beaver territories, 51 beaver dams), an overview of the dam building activities of beavers in the streams of Bavaria was obtained. Our findings revealed that 90% of the beaver dams were observed in small streams with a width ranging from 2 to 11 m and 59% of the streams were in a depth range of 0.5 to 1 m. These results coincide with observations from other studies, which showed water depths of less than one meter and variable widths ranging between 0.5 and 46 m [16,18,[43][44][45]. In Bavaria, beavers show similar activity patterns as observed in other regions.…”
Section: Survey and Analysis Of Beaver Territoriessupporting
confidence: 90%
“…We included studies on both beaver species. C. canadensis has a slightly higher litter size, but both species have otherwise similar life history, ecology and behaviour (reviewed by Parker et al 2012) and build dams with similar frequency (Danilov and Fyodorov 2015). Hence, we expect similar environmental effects of their dam-construction activity even though, to our knowledge, this has not formally been tested (see Parker et al 2012 for a review).…”
Section: Introductionmentioning
confidence: 89%
“…A water-level rise may considerably widen wetland areas and also change the physical, chemical, and biological conditions in the riparian zone. Both beaver species are assumed to have equivalent effects on the environment (Danilov & Fyodorov 2015), but the American beaver appears to reproduce slightly faster (Parker et al 2012).…”
Section: Reviewmentioning
confidence: 99%